Peru as a destination: Perceptions on the return and the permanence of venezuelan immigrants - Napan, Karen (2023)
For many years, specifically between the second half of the twentieth century, Venezuela was a very attractive country for many people who left their country of origin in search of a better quality of life (Domínguez et al, 2021; Ramírez, 2018; Castillo and Reguant, 2017); however, due to the social, political, economic and health crisis (Equilibrium, 2021), in recent years, Venezuelans have migrated to Spain, the United States, Italy, Portugal and various countries in South America such as Colombia, Chile, Ecuador, Brazil, Peru (Domínguez et al., 2021; Blouin, 2019; Ramírez, 2018) and, as of April 2020, the Venezuelan population in Peru was 861 000 individuals according to the Portal on Migration in Latin America and the Caribbean (2022); which positions Peru as the second destination country for Venezuelan migrants. For this reason, this article describes and analyses the motivations for choosing Peru as a destination country, and the expectations of permanence and return. This research includes the socio-cognitive approach of critical discourse analysis (CDA) (Van Dijk, 1999), specifically, the triad of discourse, cognition and society. Regarding the methodology applied, the procedures for the collection of information were two: the semi-structured interview and the collection of testimonies extracted from the virtual platform YouTube. In particular, in the cases in which interviews were carried out, the instrument was a questionnaire, the inclusion criteria for which were being of legal age and living in Peru. The main findings show that the return of Venezuelan nationals is conditional on state policies ensuring economic stability and a better quality of life in the country of origin. Likewise, their permanence in Peru depends on job opportunities and economic stability that allows them to live in dignity and support their families.